2014
DOI: 10.2320/jinstmet.j2013053
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening of Fe-36mass%Ni Low Thermal Expansion Alloy by Additions of C, V, Ti, and Cr and the Effect of Reducing Ni on Thermal Expansion

Abstract: Fe 36massNi alloy is well known as invar alloy for its low thermal expansion (LTE) near room temperature. Since its strength is relatively low and thus its application is limited, strengthening of LTE alloy has been a matter of concern for industrial use. It has been reported that the combined additions of V and C are effective for enhancing age hardness of Fe 36massNi alloy without remarkable increase in thermal expansion. However, since worldwide depletion of rare metals such as V has been making it diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…VC, NbC and Mo 2 C [13,14,20]. Nakama et al [13] reported that the invar alloy through precipitation of VC and TiC particles in the austenite matrix, together with subsequent 50% cold deformation presented the highest tensile strength of 1100 MPa, which is two times larger than that of the base Fe-36Ni alloy.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…VC, NbC and Mo 2 C [13,14,20]. Nakama et al [13] reported that the invar alloy through precipitation of VC and TiC particles in the austenite matrix, together with subsequent 50% cold deformation presented the highest tensile strength of 1100 MPa, which is two times larger than that of the base Fe-36Ni alloy.…”
Section: Introductionmentioning
confidence: 98%
“…Conventional strengthening methods, such as solid-solution strengthening [10], grain refinement [5], work hardening [8,11] and precipitation hardening [12][13][14][15][16], have been developed in invar alloys, e.g. Fe-36Ni [5,11], Fe-Ni-Co [12,17,18], Fe-Ni-Ti [19] and Fe-Ni-Mo [10,16], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The strengthening of Invar alloy through the precipitation of MC-type carbides, such as TiC, VC, and Mo 2 C, or intermetallics, such as γ'-type Ni 3 Ti and Ni 3 Al, was reported to be highly effective. Nakama et al reported a Fe-Ni-V-C Invar alloy reaches a tensile strength of 1000 MPa after a combination of solutionization, aging, which produces VC precipitates, and cold working [7,9]; the same author reported the strengthening of Invar alloy containing Ti, V, and C through TiC and VC precipitation, and achieved 1100 MPa tensile strength at peak aging condition [6]. Yahagi et al reported a Fe-Ni-Co-Ti Invar alloy strengthened by the precipitation of γ'-type Ni 3 Ti intermetallics exhibits a tensile strength of 1313 MPa after cold working [10].…”
Section: Introductionmentioning
confidence: 99%
“…The strengthening of Invar alloy can be achieved primarily through three methods: grain refinement [5], plastic deformation (and severe plastic deformation, SPD) [6], and precipitation hardening [4,[7][8][9]. Vingradov et al [8] reported that the tensile strength of Fe-36Ni Invar alloy can be increased to 912 MPa by refining the grain size to 180 nm using equal channel angular pressing (ECAP).…”
Section: Introductionmentioning
confidence: 99%
“…Fe-Ni binary alloy with a Ni content of ~36 wt.% is known as invar alloy, which shows a very low coefficient of thermal expansion (CTE) of almost zero under 100 °C [1,2,3,4]. Such an anomalous thermal expansion effect of the Fe-36Ni alloy is known as the invar effect [5].…”
Section: Introductionmentioning
confidence: 99%